Kawasaki Disease: Unusual Presentation with Retropharyngeal Involvement - Chiara Zeroli; Armela Gorica; Giulia Claire D'Aleo Canova; Monica Caruso; Paolo Castelnuovo; Francesca De Bernardi (Hindawi Limited, 2023)
Background. Kawasaki disease is an acute febrile generalized vasculitic syndrome of childhood of unknown ethology. The most severe complication may involve the hearth and include acute myocarditis with hearth failure, arrythmia, and coronary artery aneurism. The typical clinical symptoms are fever, conjunctivitis, rash, cervical lymphadenopathy, and mucocutaneous changes, and the diagnosis is made by the clinical criteria. Early use of aspirin and immunoglobuline improves symptoms and prevent heart complications. Case Presentation. A 4-year-old male presented to our attention for multiple unilateral laterocervical lymphadenopathies, odynophagia, and neck stiffness, initially treated with IV antibiotic therapy with partial resolution of symptoms. After four months he made a new ER access for cervicalgia, tonsils asymmetry, trismus, stiff neck, lameness, and phalanx hyperaemia and increase in the size of cervical lymph nodes. Radiology showed increase of lymphnodes dimension and retropharyngeal space asymmetry. The same day heart murmur appeared, so the patient underwent cardiological evaluation that documented dilation of the coronary arteries. This sign made it possible to place the diagnostic suspicion of Kawasaki disease and to start IV immunoglobulins and acetylsalicylic acid administration with prompt response. Conclusions. Kawasaki disease presents with a range of symptoms which, taken individually, are very common in childhood. One of these symptoms is represented by the swollen of neck lymph nodes. It is only clinical reasoning that leads to the correct diagnosis, and therefore, to the correct setting of the therapy, reducing the risk of complications.